Anterior Lamellar Repositioning in the Management of Meibomian Gland Inversion Secondary to Meibomian Gland Dysfunction. Issue 6 (15th February 2021) - Samia-Aly, Emma; Barua, Ankur R.; Patel, Radhika P.; Mehta, Purnima
Abstract : Purpose: To describe a simple alternative surgical approach to treat patients with Meibomian gland inversion (MGI; posterior migration of the Meibomian gland orifices) in the upper eyelid, secondary to cicatricial Meibomian gland dysfunction (MGD) not responding to maximal medical management. Methods: This was a retrospective, noncomparative, interventional case series of all patients with MGI not responding to conservative MGD treatment who underwent anterior lamellar repositioning through a skin crease incision with or without Blepharoplasty, between July 2017 and July 2019. Results: Eleven eyes of 7 patients were included in the study. All patients had a diagnosis of MGD with MGI and had been treated on average for 32 months with intensive medical therapy. Treatment included lubricants, topical ciclosporin 0.1%, topical steroids, and doxycycline. Despite intensive treatment, these patients remained symptomatic with persistent superior ocular surface staining. Following surgery, on average, the patients were followed for 23 months. Ten eyes (91%) had improvement of symptoms and superior ocular surface staining. All patients (100%) demonstrated improvement in the anatomical eversion of the eyelid margin and Meibomian gland orifice. Conclusion: A simple upper eyelid everting surgery with anterior lamellar repositioning can be effective in managing patients with MGI giving them symptomatic relief when all medical treatment fail. To the best of the authors' knowledge, this is the first case series describing this simple surgical technique in the management of this subgroup of patients. Abstract : A simple anterior lamellar repositioning can be effective in improving the signs and symptoms of patients with Meibomian gland inversion refractory to conservative Meibomian gland dysfunction treatment.